1992
DOI: 10.1039/p29920000787
|View full text |Cite
|
Sign up to set email alerts
|

Spectral properties and isomerism of nitroenamines. Part 3

Abstract: Vibrational, N M R and dynamic N M R spectra, considered together with the results of theoretical studies, provide a complete and fairly accurate quantitative picture of the isomerism affecting the nitroenamines R2R3N-C( 1 ) R'=C(2) H-NO, (R' = H, Me). The compounds with primary or secondary amino groups ( R2 and/or R3 = H) exist as solvent-dependent equilibrium mixtures of the intramolecularly hydrogenbonded Z-form and the €-form; the latter isomer can adopt the Z and/or the € conformation around the C(1)-N s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
0

Year Published

1999
1999
2010
2010

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 30 publications
2
20
0
Order By: Relevance
“…The chemical shift υ 15 N is only slightly sensitive to the change of solvent from CDCl 3 to CD 3 2 SO (Table 1). The chemical shift υ 15 N of 4-aminopent-3-en-2-one (1a) is very close to the value published 4 for 4-amino-3-methylpent-3-en-2-one ( 274.4 in C 6 D 6 ) and to the value of 274.8 found for 4-amino-3-ethylpent-3-en-2-one (1d) in CDCl 3 . Only the spectrum of 4-methylaminopent-3-en-2-one (1b) exhibited three signals (Table 1).…”
Section: N Nmr Spectra Of Enaminonessupporting
confidence: 54%
See 2 more Smart Citations
“…The chemical shift υ 15 N is only slightly sensitive to the change of solvent from CDCl 3 to CD 3 2 SO (Table 1). The chemical shift υ 15 N of 4-aminopent-3-en-2-one (1a) is very close to the value published 4 for 4-amino-3-methylpent-3-en-2-one ( 274.4 in C 6 D 6 ) and to the value of 274.8 found for 4-amino-3-ethylpent-3-en-2-one (1d) in CDCl 3 . Only the spectrum of 4-methylaminopent-3-en-2-one (1b) exhibited three signals (Table 1).…”
Section: N Nmr Spectra Of Enaminonessupporting
confidence: 54%
“…The 1 H and 13 C NMR spectra of 4-amino-3-(4-chlorophenylazo)pent-3-en-2-one have already been published. 2 The proportions of minor isomers in both compounds mentioned was low (Table 3), hence it was only possible, from the 1 H, 15 N GHMQC sequence, to determine reliably the coupling constants 1 J 15 N, 1 H of the major isomers because of the low solubility in CDCl 3 . Their values are close to those of the corresponding protons of 4-amino-3-phenylazopent-3-en-2-one ( Table 3).…”
Section: Azo Coupling With 4-aminopent-3-en-2-one (1a)mentioning
confidence: 99%
See 1 more Smart Citation
“…If there is at least one hydrogen atom at the nitrogen, then the Z-isomer contains an intramolecular hydrogen bond. The E-isomer (without this intramolecular hydrogen bond) containing two different substituents at nitrogen can exist as a pair of isomers of limited stability (their stability lies between that of conformers and the geometrical isomers) as a consequence of partial double bond character of the C-N bond [6,7]. The conjugation of the system facilitates the interconversion between the Z and the E forms.…”
mentioning
confidence: 97%
“…It is convenient to notice that compounds, 5, 8a-d, 11a,b, 14a-d, 18a-d, 21a-c, 22a-d and 23a,b can exist in either Z or E structures. However, according to the concept of push-pull alkenes that was reviewed by Sandstrom,17 where the physicochemical properties and chemical reactivity of numerous functionalized compounds of that type have been extensively studied, [18][19][20][21][22][23] and the recent studies which showed that the 4-oxothiazolidines with one and two exocyclic double bonds attached to a thiazolidine ring, respectively, exemplify typical push-pull compounds which can exist in Z/E equilibrium depending on temperature and the nature of the solvent. 24 One can say that compounds 5, 8a-d, 11a,b, 14a-d, 18a,b, 21a-c, 22a-d and 23a,b are examples of push-pull conjugated alkenes which are existing in a Z/E equilibrium mixture.…”
Section: Resultsmentioning
confidence: 99%